Perbandingan Pengaturan Pembagian Harta Bersama Pasca Perceraian Berdasarkan Kitab Undang-Undang Hukum Perdata (Burgerlijk Wetboek) dan Civil Act Korea Selatan - Nila Dilasari; Galih Bagas Soesilo; Sapardiyono Sapardiyono (Suara Edukasi Hukum, 2026)
This  study aims to analyze the comparative regulation of the division of marital property under the two legal systems and its impact on legal protection for the parties after divorce. The research is motivated by the differences in the regulation of marital property division between Indonesia and South Korea, which may lead to differences in legal protection for former spouses. The research method used is normative legal research with a statutory approach and a comparative law approach. The results show that the legal system in Indonesia emphasizes legal certainty through an equal distribution system, thereby providing clarity and assurance in dispute resolution. However, this system tends to insufficiently consider non-economic contributions in a proportional manner. In contrast, the legal system in South Korea grants greater authority to judges to determine the division based on principles of justice and the actual contributions of the parties, making it more flexible and adaptive to real conditions, but potentially leading to legal uncertainty. These differences affect the resulting legal protection, namely formal legal certainty in Indonesia and protection based on substantive justice in South Korea.